2020
DOI: 10.1007/s10902-020-00326-5
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Well-Being During the Covid-19 Pandemic: Associations with Personality and Emotion Regulation

Abstract: The present study examined how neuroticism, extraversion, and emotion regulation were related to loneliness and well-being during 6 weeks of major public life restrictions in the Covid-19 pandemic in Switzerland. Cross-sectional results from 466 participants showed that neuroticism and emotion regulation strategies were associated with higher loneliness and lower well-being. However, in contrast to prior research, associations of extraversion with loneliness and well-being were weak and were qualified by inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
109
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 55 publications
(100 reference statements)
14
109
3
3
Order By: Relevance
“…In relation to personality traits, the results are in line with other COVID-19 studies that show how emotional stability was inversely related to COVID-19 affectation (Aschwanden et al, 2020;Gubler et al, 2020) and with negative affect. Emotionally unstable individuals (i.e., individuals with high levels of neuroticism) have more dysfunctional interpersonal relationships and are less satisfied with their relationships, experience fear, depression, and guilt more often than emotionally stable individuals, and are more sensitive to social rejection cues.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In relation to personality traits, the results are in line with other COVID-19 studies that show how emotional stability was inversely related to COVID-19 affectation (Aschwanden et al, 2020;Gubler et al, 2020) and with negative affect. Emotionally unstable individuals (i.e., individuals with high levels of neuroticism) have more dysfunctional interpersonal relationships and are less satisfied with their relationships, experience fear, depression, and guilt more often than emotionally stable individuals, and are more sensitive to social rejection cues.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research suggests that psychological consequences of the pandemic depend on personality, because this predicts behavioral responses and emotional regulation strategies to cope with the COVID-19 crisis, and these can influence physical and psychological health (Aschwanden et al, 2020 ; Gubler et al, 2020 ). In fact, a study on individual differences in the psychological consequences of COVID-19 found that facets of Extraversion, Neuroticism, and Openness were among the strongest and most important predictors of psychological outcomes, even after controlling for basic sociodemographic variables such as gender and age (Modersitzki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the impact of the different personality domains, these studies suggest that Extraversion, in particular, is related to the negative appraisal of the coronavirus crisis and the measures taken to address it (see Carvalho et al, 2020;Modersitzki et al, 2020). Moreover, Neuroticism has been found to be associated with negative affect, such as anxiety, insecurity, or lower wellbeing, during the COVID-19 crisis (Gubler et al, 2020;Kroencke et al, 2020;Lippold et al, 2020) and with concerns, e.g. of becoming infected by COVID-19 (Aschwanden et al, 2020).…”
Section: Personality Differences In Dealing With the Covid-19 Pandemicmentioning
confidence: 99%
“…Although these practices are temporary, prolonged social isolation may have long-lasting impacts on consumers. In particular, the overwhelming loneliness associated with in-home lifestyle is felt by millions of people [ 9 , 10 ]. Consumers who live alone, the elderly and those with pre-existing mental illness are particularly vulnerable [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%